2012
DOI: 10.1002/gps.3783
|View full text |Cite
|
Sign up to set email alerts
|

The potential of case management for people with dementia: a commentary

Abstract: Aim: To propose a research agenda on case management for people with dementia.Background: A recent review of studies of case management in dementia argues that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…11,23 This study examined the impact of the PDC intervention on VHA health care costs. In our study, the model-adjusted costs for veterans receiving the PDC intervention were not significantly higher than those for the veterans in the control arm, while, as we have documented elsewhere, veterans and their caregivers receiving PDC showed improvements in care outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…11,23 This study examined the impact of the PDC intervention on VHA health care costs. In our study, the model-adjusted costs for veterans receiving the PDC intervention were not significantly higher than those for the veterans in the control arm, while, as we have documented elsewhere, veterans and their caregivers receiving PDC showed improvements in care outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of systematic reviews have been reported of studies assessing the impact of case management on older people with dementia. [183][184][185][186][187][188][189] In general, studies have provided conflicting information about the potential benefits and duration of effect of case management for people with dementia. A recent Cochrane review of case management for PLWD found that the case management group was significantly less likely to be institutionalised at 6 and 12 months than those not receiving case management, although the longer-term effects were uncertain.…”
Section: Co-ordination and Navigationmentioning
confidence: 99%
“…191 Furthermore, it is not clear which population of people with dementia is most likely to benefit from case management and at what stage of the dementia trajectory. 185 Studies have, however, identified a number of characteristics that appear to be important for the success of case management and care co-ordination. These include strong provider and care networks, good personal connections with other HCPs, expert knowledge, embedding in the multidisciplinary team, the involvement of GPs, intensive and proactive approaches and clearly defined skills and responsibilities.…”
Section: Co-ordination and Navigationmentioning
confidence: 99%
“…A systematic review of models of care for depression suggested that components that were found to significantly predict improvement were (1) the revision of professional roles; (2) the provision of a case manager who provided direct feedback and delivered a psychological therapy; and (3) an intervention that incorporated patient preferences into care. 23 The evidence base A literature review 24 published as part of the preliminary work for this study provided a commentary on case management interventions for people with dementia and a summary of its findings are provided here. The review set out to address (1) what are case managers and how do they relate to dementia care; (2) whether or not dementia care can be improved by case management; (3) what people with dementia and their carers want from a case manager and whether or not this can be provided; (4) whether or not we can measure the cost-effectiveness of case management; and (5) what direction research into case management needs to take.…”
Section: Care Co-ordinationmentioning
confidence: 99%